2017
DOI: 10.1371/journal.pone.0188950
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of paediatric chronic suppurative otitis media and hearing impairment in rural Malawi: A cross-sectional survey

Abstract: ObjectiveTo estimate the prevalence of World Health Organization-defined chronic suppurative otitis media (CSOM) and mild hearing impairment in a population representative sample of school-entry age children in rural Malawi. A secondary objective was to explore factors associated with CSOM in this population.MethodsWe performed a community-based cross-sectional study of children aged 4–6 years in Chikhwawa District, Southern Malawi, utilising a village-level cluster design. Participants underwent a structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 28 publications
2
56
0
2
Order By: Relevance
“…The consequences of OM in low-and middle-income countries (LMIC), such as hearing impairment (HI), intracranial complications and death, are particularly linked to CSOM [4]. CSOM is a significant cause of preventable HI and a leading cause of HI in school-aged children in Africa [4,11,12]. In Africa, HI seems to persist later in school years even though the CSOM had successfully healed [13].…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of OM in low-and middle-income countries (LMIC), such as hearing impairment (HI), intracranial complications and death, are particularly linked to CSOM [4]. CSOM is a significant cause of preventable HI and a leading cause of HI in school-aged children in Africa [4,11,12]. In Africa, HI seems to persist later in school years even though the CSOM had successfully healed [13].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, studies have indicated a higher prevalence in younger children (less than 6 years) and older children (more than 12 years). 9,10 Our cohort had a median age of 7.7 years with only a small portion younger than the age of six or older than 12 (Figure 1). Thus, the most commonly affected age groups were under-represented in our study.…”
Section: Discussionmentioning
confidence: 99%
“…1 Prevalence estimates of CSOM in sub-Saharan Africa range from less than one per cent to more than five per cent of the population. [8][9][10][11][12][13][14][15] However, the number of studies on this is limited and there is great variability in methodology, disease definition and sampling strategy, making precise estimates for the region challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Khairi et al 24 reported that 88.9% of the children with hearing loss had CHL. Hunt et al 25 determined the percentage of unilateral and bilateral CHL, and the results were 24.5% and 12.5% respectively. However, Bess et al 19 found different results: in their study, the rate of SNHL was of 5.4%, and the rate of CHL was of 3.4%.…”
Section: Discussionmentioning
confidence: 99%